Perspective Trends in the Study of Blood Donation and its Components as a Social Phenomenon - Kuleshov, Oleksandr (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
Donation of blood and blood components at present stage is intended not only to ensure the effective functioning of many branches of medicine, but also is a necessary condition for the development of hightech methods of providing health care. The only source of blood products are donors, thus work with them for the blood service is as relevant as solution of technological issues related to donation. The author considers the blood donation as a social phenomenon that should be studied from the perspective of sociology. The results of the national survey conducted by the Center for Sociological and Political Studies of the Belarusian State University (Belarus, Minsk) in October, 2012 are presented. The author suggests that monetary stimulation of donor activity should not be regarded as sufficient and the only one, conclusion on the need to form positive attitudes of the population towards donation from childhood is made. It is noted that the group of potential primary donors is more willing to visit the blood bank, than a group of former donors. The paper outlines the further study of blood donation and its components as a social phenomenon.